Slumdog millionaire - Vikas Swarup (Great Britain Black Swan, 2004)
SLUMDOG MILLIONAIRE is the story of Jamal Malik, an 18 year-old orphan from the slums of Mumbai, who is about to experience the biggest day of his life. With the whole nation watching, he is just one question away from winning a staggering 20 million rupees on India's 'Who Wants to Be a Millionaire?' But when the show breaks for the night, police arrest him on suspicion of cheating; how could a street kid know so much? Desperate to prove his innocence, Jamal tells the story of his life in the slum where he and his brother grew up, of their adventures together on the road, of vicious encounters with local gangs, and of Latika, the girl he loved and lost. Starring Dev Patel, Anil Kapoor, Irrfan Khan, Madhur Mittal, Freida Pinto Director Danny Boyle Special Features: Anamorphic Widescreen - 2.35 Audio: Dolby Digital 5.1 - English Dolby Digital Surround - French Subtitles - English, French, Spanish Additional Release Material: Deleted Scenes: 12 Deleted Scenes Trailers: Forced Trailers: NOTORIOUS, S. DARKO, BOTTLE SHOCK, THE OTHER END OF THE LINE Featurette: Slumdog Cutdown Documentary: Slumdog Dreams: Danny Boyle & the Making of SLUMDOG MILLIONAIRE Runtime: 120 Minutes.
Keywords: Slumdog; millionaire